1979
DOI: 10.1042/bj1770063
|View full text |Cite
|
Sign up to set email alerts
|

Diamine-induced inhibition of liver ornithine decarboxylase

Abstract: Repeated injections of 1,3-diaminopropane, a potent inhibitor of mammalian ornithine decarboxylase, induced protein-synthesis-dependent formation of macromolecular inhibitors or ;antienzymes' [Heller, Fong & Canellakis (1976) Proc. Natl. Acad. Sci. U.S.A.73, 1858-1862] to ornithine decarboxylase in normal rat liver. Addition of the macromolecular inhibitors, produced in response to repeated injections of diaminopropane, to active ornithine decarboxylase in vitro resulted in a profound loss of the enzyme activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
23
0

Year Published

1981
1981
1986
1986

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 23 publications
5
23
0
Order By: Relevance
“…Several of these individual results have been confirmed and extended by other laboratories (McCann et al, 1977;Friedman et al, 1977;Jefferson and Pegg, 1977;Poso et al, 1978;Kallio et al, 1979). McCann et al, (1977) have also demonstrated the in vivo existence of the "ODC-antizyme" complex in HTC cells.…”
supporting
confidence: 56%
“…Several of these individual results have been confirmed and extended by other laboratories (McCann et al, 1977;Friedman et al, 1977;Jefferson and Pegg, 1977;Poso et al, 1978;Kallio et al, 1979). McCann et al, (1977) have also demonstrated the in vivo existence of the "ODC-antizyme" complex in HTC cells.…”
supporting
confidence: 56%
“…However, the delayed appearance of the protein inhibitor of L-ornithine decarboxylase (Fig. 9), is most likely a secondary inhibitory mechanism which is out of phase with the observed induction-repression cycle, as also concluded by others [14]. It was shown that polyamines activate the enzymatic synthesis of nuclear poly(adenosine diphosphoribose) [49].…”
Section: Discussionmentioning
confidence: 87%
“…Evidence has been presented to suggest that the external polyamines may induce the loss of ornithine decarboxylase activity through the stimulation of the production of a protein (antizyme) which specifically binds and inactivates this enzyme [6-81. Other investigators, however, feel that the formation of this antizyme is not functional in the rapid decay in enzyme activity [9,10]. Although this sensitivity to exogenous polyamines has now been Enzyme.…”
mentioning
confidence: 99%